Community Structure and Social Interaction of Timor Deer (Cervus Timorensis) in Tasikoki Animal Rescue Center, Bitung City, North Sulawesi - Sapulete, Elizabeth; Wahyudi, Lalu; Umboh, Stella (International Journal of Biosystem Research, 2026)
The Timor Deer (Cervus timorensis) is an endemic species of Indonesia classified as vulnerable by the IUCN due to deforestation, habitat degradation, and poaching. As a social animal, the community structure and dynamics of Timor Deer interactions influence reproductive success and population sustainability. The Tasikoki Wildlife Rescue Center (PPST) in Bitung City, North Sulawesi, is an ex-situ conservation facility that houses and rehabilitates Timor Deer as part of efforts to conserve this protected species. This study aims to analyze the community structure and describe the daily social interactions of Timor deer at PPST. Observations were conducted over 10 days using the focal animal sampling method for 12 hours per day (06:00–18:00 WITA) on a single group consisting of 21 individuals. The results of the study indicate that the community structure of Timor deer at PPST consists of 21 individuals divided into three age categories: 6 adults, 9 sub-adults, and 6 juveniles, with a male-to-female ratio of 1:1.14. One dominant male was identified as the alpha (Individual A), who leads the group and has priority access to food and females. The resulting social hierarchy reflects the natural patterns of Cervus timorensis, characterized by a linear dominance system. Daily social interactions within the Timor deer community at PPST were dominated by agonistic behaviors, totaling 27 incidents (51.9%) including fighting, chasing, chasing away, threatening, and butting as well as affiliative behaviors, totaling 25 incidents (48.1%) including grooming, following, and copulation attempts. Agonistic behavior was triggered primarily by competition for food access, whereas affiliative behavior occurred more frequently between adult females and juveniles, reflecting the pattern of collective care within the group.